Rhodes University during the segregation and apartheid eras, 1933 to 1990 - Greyling, Sean Andrew (Rhodes University, Faculty of Humanities, Department of History, 2008)
In 2004 Rhodes University celebrated its centenary. At a Critical Tradition Colloquium opportunity was given to explore the university's past. In particular, its liberal image was questioned and its role during apartheid brought under scrutiny. This thesis investigates the questions raised at the Colloquium. It aims to cover the whole apartheid era in one coherent narrative by addressing the history of Rhodes during that era and how it handled issues of race and politics. It begins in 1933, when the first black student applied to Rhodes, and ends in 1990, when apartheid was drawing to a close.
Keywords: Rhodes University -- History; Post-apartheid era -- South Africa -- History; College students -- South Africa -- Political activity; South Africa -- Race relations -- History -- 20th century; South Africa -- Politics and government -- 20th century